RESPON PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Vigna radiata L.) TERHADAP PEMBERIAN TRICHOKOMPOS LIMBAH AMPAS SAGU - Gata Rama Febrianto; Husna Yetti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aimed to determine the effect of sago palm and pulp waste trichocompost get a dose of sago pulp waste trichocompost best in increasing the growth and yield of green beans. Research conducted experimentally using a randomized block design (RBD), which consists of 5 treatments and 4 replications ie S0: Without Trichocompost waste sago, S1: Sago waste 15 tonnes/ha equivalent to 3 kg/2m2, S2: Trichocompost sago waste 12.5 tonnes/ha equivalent to 2,5 kg/2m2, S3: Trichokompos sago waste15 tonnes/ha equivalent to 3 kg/2m2 and S4: Trichocompost sago waste 17,5 tonnes/ha equivalent to 3,5 kg/2m2. The results those significant according to ANOVA, followed by Duncan's multiple range test at 5% level. Parameters measured were plant height, number of primary branches, flowering age, harvesting age, number of pods per plant, percentage pithy pods, seed weight per plot and weight of 1000 seeds. The results showed that application of trichocompost sago pulp waste on green bean plants increased plant height, number of primary branches, number of pods per plant, percentage pithy pods, seed weight per plot and weight of 1000 seeds. Giving trichocompost sago waste pulp at a dose of 17,5 tonnes/ha gives the highest yield in the number of primary branches, the percentage of peas pithy and weight of 1000 seeds. While the administration at a dose of 15 ton/ha gives the highest yield on plant height, number of pods per plant and seed weight per plot. Keywords: green beans, sago pulp waste, Trichocompost